Effect of gender and age in fear and stress due to COVID-19. Issue 1 (19th May 2021) - Bisht, Ila Pant; Bisht, Raj Kishor; Sagar, Priyanka
ABSTRACT: The entry of COVID-19 created an unprecedented environment of fear in society. Life during lockdown may have a significant effect on the mental and physical health of human beings. The present study aims to analyze the effect of gender and age group in deciding the level of fear and stress due to COVID-19. We conducted an online survey in the Uttarakhand state of India for the present study. Chi–square test of independence has been used for establishing dependency of various factors like fear/stress on gender and age group. We find that fear of COVID-19 is independent of gender as well as age group. Stress is independent of gender but depends on age group with elder people having less stress in comparison to young people.